ΤΕΧΝΗΣ ΕΥΡΗΜΑΤΑ. Motyw wynalazków kulinarnych w komedii średniej i nowej oraz poezji gastronomicznej - Stuligrosz, Magdalena (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2021)
The purpose of this paper is to show how Middle and New comedy as well as gastronomic poetry authors use the protos heuretes-motif characteristic of literature undertaking heurematographic themes, to present the originality and innovation of the cook’s and parasite’s art.